Familial Blue Rubber Bleb Nevus Syndrome in Pregnancy with Spinal Epidural Involvement - Daigo Ochiai; Kei Miyakoshi; Kazumi Yakubo; Tatsuro Fukuiya; Yasunori Yoshimura (Case Reports in Obstetrics and Gynecology)
Blue rubber bleb nevus syndrome (BRBNS) is a rare vascular disorder characterized by multiple venous malformations (VMs) of the skin, gastrointestinal tract, and other organs. To date, several cases of sporadic BRBNS involving various parts of the pregnant woman’s body have been reported; however, BRBNS in pregnancy with spinal epidural involvement has not been reported. Here, we describe the clinical features and management of familial BRBNS in pregnancy. The patient presented with multiple VMs on her head, neck, floor of the mouth, trunk, leg, foot, and vulva and spinal epidural lesions. The patient’s mother and sister also exhibited multiple VMs similar lesions, indicating a familial form of BRBNS. Cesarean section under general anesthesia was performed, and a healthy male neonate was delivered. The mother’s postoperative course was uneventful and her VMs decreased in size after delivery. Physicians should consider the possibility of systemic diseases and familial inheritance in cases of VMs.